Bela Negara Dalam Perspektif Al- Qur’an (Tinjauan Analisis Teori Dan Praktik) - Suhaidi (Jurnal Pendidikan Agama Islam, 2025)
The issue of national defense in Islam in Indonesia is indeed quite complex. National defense is not only a geographical issue, but also a matter of local and cultural values ​​that should serve as a bridge between Islamic values ​​and statehood. "Defending the country in another form is loving the homeland as we love our own mother." The concept of jihad in Islam is often misunderstood. For others, this concept is often interpreted as a concept of genocide or the extermination of those who differ from the truth (aqidah) of Islam. Therefore, the word jihad often becomes a threat to those who do not share the Islamic faith. This gives rise to Islamophobia, fear and anti-Islam. Among Muslims themselves, some narrow the definition of jihad by attempting to eliminate anyone who differs from themselves, with their understanding and beliefs, if necessary by violence.